Chat network study and design using HTML and PHP web programming - ‪Angham Khalid Hussein ‬‏ (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Chat rooms becoming a part of human life, from sharing and exchanging information such as texts, pictures and messages. Many begin to share the latest news and images related to news in the media field as well as chat messaging in the Internet and targeting customers in business, jokes, music and video in the entertainment field. In this paper a chat web site are designed using Hyper Text Markup language (HTML) and Personal Home Page (PHP) web programming languages with security and authentication features added to it to keep user privacy and personal information unattached, and Apache http server are used to test it.